White matter hyperintensities in bipolar disorder: systematic review and meta-analysis - Silva, Tânia; Nunes, Cesar; Ribeiro, Andreia; Santana, Isabel; Cerejeira, Joaquim (Frontiers in Psychiatry, 2024)
White matter hyperintensities are lesions of presumed vascular origin associated with Cerebral small vessel disease. WMH are common findings that and are associated with increased risk of cognitive impairment and dementia. A higher prevalence of WMH has been also reported in patients with Bipolar Disorder (BD), although the evidence is conflicting.To compare the prevalence of WMH in adults with BD, with the prevalence found in healthy controls.We searched the Embase, Medline/PubMed, and references cited in articles retrieved on May 20, 2023. We included case-control studies that compared the prevalence of WMH in adult BD patients with the prevalence of WMH in healthy controls, using T2weighted magnetic resonance imaging. We performed a meta-analysis using a random-effects method based on the inverse-variance approach.We included 22 case-control studies reporting data of 1313 people. The overall rate of WMH was 46.5% in BD patients and 28% in controls (pooled Odds Ratio 2.89, 95% CI 1.76; 4.75). We found a moderate heterogeneity across studies (I 2 =0.49). Publication bias was not significant.We found evidence that BD patients have a higher burden of WMH than healthy controls. Main limitations were impossibility of analyzing gender differences and bipolar type, moderate heterogeneity between studies, non-representative samples, lack of control for major confounders and search in two electronic databases.